La Iglesia católica y la formación del Estado-nación en América Latina en el siglo XIX: El caso colombiano - Ortiz Mesa, Luis Javier (2022)
The article examines the role of the Catholic Church in the formation of theColombia Nation State in three distinct periods during the 19th-century.In the first period (1810-1853) the members of the Church have an activeparticipation in the processes of independence (1810 and 1824). Given thedecisive role of the Church in the formation of new mentalities since thecolonial times and in the also in the formation of parties, between 1824 and1853 the nascent State subjugated the Church to the Republican patronage.A second period, with difficult processes of secularization during the Liberalgovernments, departed from the separation of the Church and State in 1853and culminated in 1885. Finally, a third period shows the recovery of thedominant role of the Catholic Church in the Colombian society under theconservative regeneration, between 1886 and 1902. The Colombia processran against the processes of secularization that happened in the other LatinAmerica countries.